2013
DOI: 10.1016/j.jconrel.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

PK modulation of haptenylated peptides via non-covalent antibody complexation

Abstract: We applied noncovalent complexes of digoxigenin (Dig) binding antibodies with digoxigeninylated peptide derivatives to modulate their pharmacokinetic properties. A peptide derivative which activates the Y2R receptor was selectively mono-digoxigeninylated by reacting a NHS-Dig derivative with an ε-amino group of lysine 2. This position tolerates modifications without destroying receptor binding and functionality of the peptide. Dig-peptide derivatives can be loaded onto Dig-binding IgGs in a simple and robust r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…One objective to covalently link payloads to hapten binding antibodies is to increase the stability between payload and antibody in vivo . We have previously shown that noncovalent connections between antibodies and haptenylated payloads can be applied to prolong the serum half-life of small compounds and peptides ( 17 ). In these experiments, we observed a profound increase of the serum half-life of the payload, and we also observed release of the noncovalently linked payload from the antibody after extended periods of time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One objective to covalently link payloads to hapten binding antibodies is to increase the stability between payload and antibody in vivo . We have previously shown that noncovalent connections between antibodies and haptenylated payloads can be applied to prolong the serum half-life of small compounds and peptides ( 17 ). In these experiments, we observed a profound increase of the serum half-life of the payload, and we also observed release of the noncovalently linked payload from the antibody after extended periods of time.…”
Section: Resultsmentioning
confidence: 99%
“…Final cleavage was performed as described above. The crude product was purified by preparative reversed phase HPLC as previously described ( 17 ) giving a colorless solid ( m / z : calculated for C131H197N39O30S2 = 2862.4; found: 2862.4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These animals were treated with different NPY2 receptor agonists, known to be able to modulate the obese phenotype (provided active concentrations can be achieved for sufficient time) . Hoffmann and coworkers could demonstrate that the peptide PYY or Dig‐coupled PYY derivatives by itself had very limited potency (due to rapid elimination), but had improved potency when it was complexed with an anti‐digoxigenin antibody . Obese mice treated with the PYY‐Dig–antibody complexes showed reduced food intake even after 48 h, whereas peptide alone showed efficacy only in the first hour after treatment .…”
Section: Hapten‐binding Iggs For Modulation Of Pharmacokinetic Propermentioning
confidence: 99%